Heat treatment method for additive manufacturing of nickel-based superalloy
Through the triple heat treatment process of additively manufactured nickel-based high-temperature alloy, the problems of element segregation, uneven structure and high residual stress in additively manufactured nickel-based high-temperature alloys in high-temperature service were solved, and the high-temperature mechanical properties of the alloy were improved.
Patent Information
- Application Number
- CN202411459382.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-07
AI Technical Summary
Additive manufacturing nickel-based high-temperature alloys have problems such as element segregation, uneven structure and high residual stress during high-temperature service, resulting in unstable performance and cannot meet the application needs in long-term high-temperature environments.
Triple heat treatment process is adopted, including stress removal annealing treatment, solid solution treatment and aging treatment. The stress-relieving annealing treatment reduces residual stress through two-step step annealing, and the solid solution treatment achieves uniform precipitation of the γ′ phase at high temperature, and the aging treatment regulates the cubicity and grain size of the γ′ phase.
The γ′ phase volume fraction and grain size of nickel-based high-temperature alloy are significantly improved, residual stress is eliminated, the uniformity and strength of the structure are improved, and the high-temperature mechanical properties of the alloy are improved.
Smart Images

Figure CN119392134A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of additive manufacturing, and in particular to a heat treatment method for additively manufacturing a nickel-based high-temperature alloy. Background Art
[0002] Nickel-based superalloys are key hot-end components (such as turbine blades, turbine disks, combustion chambers, and casings) of modern aero-engines and gas turbines due to their excellent high-temperature performance and stability, and are widely used in the preparation of various high-temperature parts. In order to meet the requirements of thrust-to-weight ratio and thermal efficiency of the new generation of high-performance aero-engines, the structural design of key hot-end components of superalloys such as turbine blades is becoming increasingly complex, which poses a challenge to traditional molding processes such as casting, forging, and powder metallurgy. Additive manufacturing technology has the process characteristics of integration and near-net shaping, and has obvious advantages and advancement in the preparation of complex structure superalloy hot-end components. However, for high-performance, high-temperature nickel-based superalloys with high γ′ phase volume fraction, due to their high content of γ′ phase-forming elements such as Al, Ti, Ta, and Nb, even if the ultra-high temperature gradient unique to additive manufacturing can significantly inhibit element segregation, the inherent thermal cycle phenomenon that occurs with the increase in build height will still cause element segregation in the alloy deposited structure, thereby forming weak organizational structures such as dendrites, eutectics, and large-sized carbides under high-temperature service. In addition, due to the rapid solidification and cooling process of additive manufacturing, the precipitation of γ′ phase in the deposited structure is suppressed or the precipitation morphology is spherical and small in size, which cannot achieve the effect of strengthening the alloy performance at high temperature. At the same time, the rapid cold-hot transition in the additive manufacturing process often causes complex thermal stress and phase precipitation to remain in the deposited alloy, resulting in phase change stress. The overall residual stress level is much higher than that of traditional cast high-temperature alloys, which can easily lead to recrystallization and damage the alloy performance when serving at high temperatures. Therefore, the microstructure of the deposited alloy sample prepared by additive manufacturing is unstable and uneven, and it is impossible to give full play to the potential performance of the alloy and meet the service requirements of the hot end components of engines and gas turbines that work for a long time at high temperatures, harsh environments, and complex stress states. It is necessary to perform reasonable heat treatment to achieve the precipitation of γ′ phase with high cubicity, suitable size, high percentage and uniform distribution, eliminate residual stress and segregation to obtain uniform microstructure characteristics, make the grains coarsened and reduce the number of grain boundaries and other microstructure regulation. Finally, the alloy performance, especially the optimization of performance at high temperature, is achieved, and the application range of additive manufacturing high-temperature alloys is expanded.
[0003] At present, although some heat treatment methods for additively manufactured nickel-based superalloys have been reported, most of them are alloys such as IN718, IN625 and GH3536 that serve at medium and low temperatures. The content of alloying elements such as Al, Ti, Ta, and Nb is low, resulting in only slight element segregation in the alloy, and the types of precipitated phases are small and the content is low. Therefore, the homogenization difficulty is small, and there is no need for excessive regulation of strengthening phase characteristics. The overall heat treatment steps are relatively simple, and they are not completely suitable for high-performance, high-temperature additively manufactured nickel-based superalloys with high γ′ phase volume fraction. However, due to the slow cooling rate of the traditional cast superalloy preparation process, the dendrites are coarse, the eutectic content is high, and the stress level is low, which is very different from the deposited microstructure of the above-mentioned additively manufactured superalloy. Therefore, it is not appropriate to continue to use the heat treatment system formulated for cast superalloys, especially the high-temperature heat treatment process is very likely to cause concentrated release of residual stress, thereby causing cracking and recrystallization.
[0004] In summary, there is an urgent need for a heat treatment method for additively manufactured high-temperature alloys to increase the volume fraction of the γ′ phase of the additively manufactured high-temperature alloys, obtain a γ′ phase of suitable size, and eliminate cracking and recrystallization caused by residual stress, thereby improving the high-temperature mechanical properties of additively manufactured nickel-based high-temperature alloys. Summary of the invention
[0005] In view of this, the present invention provides a heat treatment method for additively manufactured nickel-based high-temperature alloys, the main purpose of which is to increase the volume fraction of the γ′ phase of the alloy, obtain a γ′ phase of suitable size, and eliminate cracking and recrystallization caused by residual stress.
[0006] In order to achieve the above object, the present invention mainly provides the following technical solutions:
[0007] In one aspect, an embodiment of the present invention provides a heat treatment method for additively manufacturing a nickel-based high-temperature alloy, comprising the following steps:
[0008] Stress relief annealing treatment: placing the additively manufactured nickel-based high-temperature alloy at a first temperature for a first step of stress relief annealing treatment; then heating it to a second temperature for a second step of stress relief annealing treatment, and after cooling, obtaining the additively manufactured nickel-based high-temperature alloy after the stress relief annealing treatment; wherein the first temperature is 850-890°C, and the second temperature is 900-950°C; the second temperature is higher than the first temperature;
[0009] Solution treatment: performing a solution treatment on the additively manufactured nickel-based high-temperature alloy after the stress relief annealing treatment to obtain the additively manufactured nickel-based high-temperature alloy after the solution treatment;
[0010] Aging treatment: performing aging treatment on the additively manufactured nickel-based high-temperature alloy after the solid solution treatment to obtain the additively manufactured nickel-based high-temperature alloy after heat treatment.
[0011] Preferably, in the step of stress relief annealing treatment: the time of the first step stress relief annealing treatment is 1-2 hours; and / or the time of the second step stress relief annealing treatment is 1-2 hours; and / or the cooling method is air cooling, and cooling to room temperature.
[0012] Preferably, in the step of stress relief annealing treatment: the heat treatment furnace is heated to 850-890°C, the additively manufactured nickel-based high-temperature alloy is placed in the heat treatment furnace for the first step of stress relief annealing treatment, and the insulation treatment time is 1-2h; then, the furnace is heated to 900-950°C and then the second step of stress relief annealing treatment is carried out, and the insulation treatment time is 1-2h; finally, it is taken out for air cooling and cooled to room temperature.
[0013] Preferably, in the step of solid solution treatment: the additively manufactured nickel-based high-temperature alloy after stress relief annealing is placed at a temperature of 1250-1280°C for solid solution treatment, and then cooled to obtain the additively manufactured nickel-based high-temperature alloy after solid solution treatment; preferably, the solid solution treatment time is 1-2h; preferably, the cooling method is air cooling.
[0014] Preferably, the aging treatment step includes:
[0015] The first step of aging treatment: placing the additively manufactured nickel-based high-temperature alloy after the solid solution treatment at a temperature of 1050-1120° C. for the first step of aging treatment; after cooling, the additively manufactured nickel-based high-temperature alloy after the first step of aging treatment is obtained;
[0016] The second step of aging treatment: placing the additively manufactured nickel-based high-temperature alloy after the first step of aging treatment at 850-870°C for the second step of aging treatment; after cooling, the additively manufactured high-temperature alloy after heat treatment is obtained;
[0017] Preferably, the cooling method is air cooling;
[0018] Preferably, cooling to room temperature.
[0019] Preferably, in the aging treatment step: the temperature of the first aging treatment is 4-6 h; and / or the temperature of the second aging treatment is 16-20 h.
[0020] Preferably, the additively manufactured nickel-based high-temperature alloy comprises the following chemical components, in terms of weight percentage: Cr 6.5-9.5wt%, Co 6.5-9.5wt%, W 6.5-9.5wt%, Mo 1.0-2.5wt%, Al 4.0-5.5wt%, Ti 0.5-1.5wt%, Ta 4.5-6.0wt%, C 0.01-0.1wt%, B 0.01-0.1wt%, and the balance is Ni.
[0021] Preferably, the additively manufactured nickel-based high-temperature alloy is a deposited additively manufactured nickel-based high-temperature alloy; preferably, the additively manufactured nickel-based high-temperature alloy is a deposited additively manufactured nickel-based high-temperature alloy prepared by laser direct energy deposition and selective laser melting; preferably, if the additively manufactured nickel-based high-temperature alloy is a laser direct energy deposited alloy, then in the deposited structure: the average grain size is 80-100μm, there is dendrite segregation, wherein the primary dendrite spacing is 20-30μm; preferably, if the additively manufactured nickel-based high-temperature alloy is a selective laser melting deposited alloy, then in the deposited structure: the average grain size is 20-50μm, there is a cellular structure and dendrites with a spacing of 5-10μm (specifically, the cellular structure is dominant, and there are small, underdeveloped dendrites with a primary dendrite spacing of 5-10μm).
[0022] On the other hand, an embodiment of the present invention provides an additively manufactured nickel-based high-temperature alloy after heat treatment, characterized in that the additively manufactured nickel-based high-temperature alloy after heat treatment is obtained by heat treating the additively manufactured nickel-based high-temperature alloy using the heat treatment method for additively manufactured nickel-based high-temperature alloy described in any of the above items.
[0023] Preferably, in the additively manufactured nickel-based high-temperature alloy after the heat treatment: the alloy structure is completely crack-free, the average size of the γ' phase is 0.3 μm-0.5 μm, the volume fraction is 55-65 vol%, and the average grain size is 100-200 μm;
[0024] Preferably, the tensile properties of the additively manufactured nickel-based high-temperature alloy satisfy: at room temperature, σ b ≥1100MPa,σ 0.2 ≥900MPa, A≥10%; at 760℃±5℃, σ b ≥1050MPa,σ 0.2 ≥850MPa, A≥8%; at 1000℃±5℃, σ b ≥480MPa,σ 0.2 ≥290MPa, A≥8%.
[0025] Compared with the prior art, the heat treatment method for additively manufacturing nickel-based high-temperature alloys of the present invention has at least the following beneficial effects:
[0026] The embodiment of the present invention provides a heat treatment method for additively manufactured nickel-based high-temperature alloys, which sequentially performs stress relief annealing, solution treatment, and aging treatment on the additively manufactured high-temperature alloys. Here, the present invention designs the stress relief annealing treatment into a two-step stress relief annealing treatment, that is, firstly, a preliminary stress relief annealing treatment is performed in a lower temperature range of 850-890°C; then, the temperature is raised to 900-950°C with the furnace and then a subsequent stress relief annealing treatment is performed, so that the stress can be prevented from being concentratedly released along the defective area (mainly cracks) under the action of external heat, but is released in a slow manner, so as to suppress the cracking of the sample while achieving efficient reduction of the alloy stress level in a short time. Then, on the basis of the stress relief annealing treatment, the solid solution treatment and aging treatment steps are combined to achieve an increase in the volume fraction of the γ′ phase of the additively manufactured nickel-based high-temperature alloy, obtain a γ′ phase with high cubicity and suitable size, eliminate cracking and recrystallization caused by residual stress, and coarsen the grain size, thereby improving the high-temperature mechanical properties of the additively manufactured nickel-based high-temperature alloy.
[0027] Furthermore, in the prior art, the solution treatment temperature of traditional high-performance casting high-temperature alloys is generally selected to be 10-20°C lower than the initial melting temperature of the alloy to ensure a higher solution treatment temperature and achieve complete elimination of segregation and eutectic. However, additively manufactured high-temperature alloys have low segregation and less eutectic precipitation, so effective organization control can still be achieved when the solution treatment temperature is low and the time is short. The final solution treatment temperature of the alloy is selected to be 50-80°C lower than the initial melting temperature, that is, 1250-1280°C. In order to obtain a γ′ phase with high cubicity, high content, uniform distribution and appropriate size, a two-step aging treatment is required, in which the first step of aging treatment can effectively control the size of the γ′ phase, and the second step of aging treatment can effectively control the cubicity of the γ′ phase. The entire aging process can fully precipitate a large amount of γ′ phase. Since the alloy structure tends to be stable after stress relief + solution treatment, and the aging temperature is relatively low and has little effect on other organizational structures, the temperature and time of the two-step aging treatment are determined as follows: the first step aging treatment is 1050-1120℃ / 4-6h, and the second step aging treatment is 850-870℃ / 16-20h.
[0028] In summary, the present invention improves the volume fraction of the γ′ phase of the additively manufactured nickel-based high-temperature alloy through multi-step heat treatment, obtains a γ′ phase with high cubicity and suitable size, eliminates cracking and recrystallization caused by residual stress, and coarsens the grain size, thereby improving the organization, reducing defects, weak organizational structures such as grain boundaries, and achieving the improvement of tensile and endurance performance at high temperatures above 900°C, thereby achieving the purpose of optimizing alloy performance; the heat treatment process of the present invention is applicable to additively manufactured nickel-based high-temperature alloy samples prepared by selective laser melting and laser direct energy deposition, and has a certain degree of universality. The heat treatment method of the present invention does not require special environments such as vacuum and argon, so it has the characteristics of simplicity, low cost, high efficiency, etc., and is an effective way to optimize the organization and performance of additively manufactured nickel-based high-temperature alloys.
[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is the printed structure of the nickel-based high-temperature alloy manufactured by additive manufacturing. (a) is the deposited structure of the sample prepared by the laser direct energy deposition process, and (b) is the deposited structure of the sample prepared by the laser selective melting process.
[0031] Figure 2 is an alloy structure diagram of the additively manufactured nickel-based high-temperature alloy sample after heat treatment in Example 1; wherein (a) is the alloy structure at low magnification; (b) is the alloy structure at high magnification;
[0032] Figure 3 1 is an alloy structure diagram of the additively manufactured nickel-based high-temperature alloy sample after heat treatment in Example 2; wherein (a) is the alloy structure at low magnification; (b) is the alloy structure at high magnification;
[0033] Figure 4 1 is an alloy structure diagram of the additively manufactured nickel-based high-temperature alloy sample after heat treatment in Example 3; wherein (a) is the alloy structure at low magnification; (b) is the alloy structure at high magnification;
[0034] Figure 5 It is the alloy structure diagram of the additively manufactured nickel-based high-temperature alloy sample after heat treatment in Example 4; wherein (a) is the alloy structure at low magnification; (b) is the alloy structure at high magnification. DETAILED DESCRIPTION
[0035] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention application are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0036] The present invention provides a heat treatment method for additively manufactured nickel-based high-temperature alloys (with high γ′ phase content) to further increase the volume fraction of the γ′ phase of the alloy, obtain a γ′ phase with high cubicity and suitable size, eliminate cracking and recrystallization caused by residual stress, and coarsen the grain size, thereby improving the high-temperature mechanical properties of the additively manufactured nickel-based high-temperature alloy. To achieve the above purpose, the technical solution of the present invention is described in detail as follows:
[0037] The present invention provides a heat treatment method for additively manufactured nickel-based high-temperature alloys, comprising: a heat treatment process method for sequentially performing triple heat treatments on the additively manufactured nickel-based high-temperature alloys, wherein the triple heat treatments are stress relief annealing treatment, short-time solid solution treatment, and two-stage aging treatment performed sequentially.
[0038] The details are as follows:
[0039] Stress relief annealing treatment: placing the additively manufactured nickel-based high-temperature alloy at a first temperature for a first step of stress relief annealing treatment; then heating it to a second temperature for a second step of stress relief annealing treatment, and after cooling, obtaining the additively manufactured nickel-based high-temperature alloy after stress relief annealing treatment; wherein the first temperature is 850-890°C, and the second temperature is 900-950°C; the second temperature is higher than the first temperature.
[0040] In this step, the first step of stress relief annealing treatment takes 1-2 hours; the second step of stress relief annealing treatment takes 1-2 hours; the cooling method is air cooling, and the cooling is performed to room temperature.
[0041] Preferably, the heat treatment furnace is heated to 850-890°C, and the additively manufactured high-temperature alloy is placed in the heat treatment furnace for the first step of stress relief annealing treatment, and the heat preservation time is 1-2 hours; then, the furnace is heated to 900-950°C and the second step of stress relief annealing treatment is performed, and the heat preservation time is 1-2 hours; finally, it is taken out for air cooling and cooled to room temperature.
[0042] It should be noted here that the present invention does not use furnace heating in the first step of stress relief annealing. Due to furnace heating, there are temperature differences between different areas in the furnace, displayed temperature and real temperature, etc., and the temperature change in the furnace is difficult to control, which can easily lead to uneven release of alloy stress and increase the risk of cracking. Therefore, the temperature is pre-heated to the target temperature, the temperature is accurately measured, and after the furnace temperature is stable, the additively manufactured high-temperature alloy is placed in the heat treatment furnace.
[0043] Solution treatment: performing solution treatment on the additively manufactured nickel-based high-temperature alloy after the stress relief annealing treatment to obtain the additively manufactured nickel-based high-temperature alloy after the solution treatment.
[0044] In this step: the heat treatment furnace is heated to 1250-1280°C, and then the additively manufactured nickel-based high-temperature alloy after stress relief annealing is placed in the furnace for short-time solid solution treatment, the heat preservation time is 1-2 hours, and then taken out for a second air cooling to cool to room temperature.
[0045] Aging treatment: performing aging treatment on the additively manufactured nickel-based high-temperature alloy after the solid solution treatment to obtain the additively manufactured nickel-based high-temperature alloy after heat treatment.
[0046] In this step, the aging treatment includes the first aging treatment and the second aging treatment.
[0047] The heat treatment furnace is cooled to 1050-1120°C, and then the additively manufactured high-temperature alloy after solution treatment is placed in the furnace for the first step of aging treatment. The insulation treatment time is 4-6 hours, and then it is taken out for air cooling and cooled to room temperature.
[0048] Subsequently, the heat treatment furnace is cooled to 850-870°C, and the additively manufactured high-temperature alloy sample after the first step of aging treatment is placed in the furnace for the second step of aging treatment. The insulation treatment time is 16-20 hours, and then taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy after heat treatment.
[0049] Preferably, after the second step of aging treatment, it also includes: characterizing the additively manufactured nickel-based high-temperature alloy after heat treatment. Preferably, the expected effects include: the alloy structure is completely crack-free, the average size of the γ' phase is 0.3μm-0.5μm, the volume fraction is 55-65vol%, and the average grain size is 100-200μm (the nickel-based high-temperature alloy structure is completely crack-free, has a uniformly distributed, cubic and high volume fraction of the γ' phase, the structure is uniform without obvious recrystallization, the average grain size is increased, and the number of grain boundaries is reduced).
[0050] Preferably, the additively manufactured nickel-based high-temperature alloy comprises the following chemical components, in terms of weight percentage: Cr 6.5-9.5wt%, Co 6.5-9.5wt%, W 6.5-9.5wt%, Mo 1.0-2.5wt%, Al 4.0-5.5wt%, Ti 0.5-1.5wt%, Ta 4.5-6.0wt%, C 0.01-0.1wt%, B 0.01-0.1wt%, and the balance is Ni.
[0051] Preferably, the additively manufactured nickel-based high-temperature alloy is a deposited additively manufactured nickel-based high-temperature alloy prepared by laser direct energy deposition and selective laser melting.
[0052] The design concept of the heat treatment system in the present invention is as follows:
[0053] 1) For additively manufactured nickel-based superalloys, although the extremely high temperature gradient severely restricts the migration of atoms, making the diffusion of alloying elements difficult, thereby reducing the precipitation of various types of precipitated phases and forming a supersaturated solid solution in the deposited structure, for additively manufactured nickel-based superalloys with high alloying degree, high γ′ phase content, and high performance, there are still weak structures such as dendrites / eutectics and uneven structures. This requires the use of reasonable heat treatment processes to control the segregation and precipitation phase characteristics, obtain good alloy structures, and give full play to the performance potential of the alloy.
[0054] 2) Considering the complex and rapid cold and heat exchange and dynamic γ′ strengthening phase precipitation in the additive manufacturing process, the alloy has a high residual stress. Therefore, it is necessary to add a stress relief annealing step before the traditional solid solution + aging heat treatment step to reduce the residual stress and avoid its concentrated release in the subsequent high-temperature solid solution process, which leads to cracking of the alloy. According to the important phase transition point temperature of the alloy obtained by DTA, it can be seen that the initial dissolution temperature of the γ′ phase of the chemical composition alloy of the present invention is 1088°C, the complete dissolution temperature is 1197°C, and the initial melting temperature is 1330°C. Considering the annealing temperature range of traditional casting high-temperature alloys, a high-temperature stress relief annealing temperature of 850-950°C is finally selected, and a step-by-step stress relief annealing treatment step is adopted, that is, firstly, a preliminary stress relief annealing treatment is carried out in a lower temperature range of 850-890°C; then, the temperature is raised to 900-950°C with the furnace and then a subsequent stress relief annealing treatment is carried out, which further avoids the concentrated release of stress and causes cracking of the sample while achieving efficient reduction of the alloy stress level in a short time.
[0055] 3) The solution treatment temperature of traditional high-performance casting high-temperature alloys is generally selected to be 10-20℃ lower than the initial melting temperature of the alloy to ensure a higher solution treatment temperature and achieve complete elimination of segregation and eutectic. However, the segregation of additively manufactured high-temperature alloys is low and the eutectic precipitation is small, so effective organization control can still be achieved when the solution treatment temperature is low and the time is short. The final solution treatment temperature of the alloy is selected to be 50-80℃ lower than the initial melting temperature, that is, 1250-1280℃. In order to obtain a γ′ phase with high cubicity, high content, uniform distribution and appropriate size, a two-step aging treatment is required, in which the first step of aging treatment can effectively control the size of the γ′ phase, and the second step of aging treatment can effectively control the cubicity of the γ′ phase. The entire aging process can fully precipitate a large amount of γ′ phase. Since the alloy structure tends to be stable after stress relief + solution treatment, and the aging temperature is relatively low and has little effect on other organizational structures, the temperature and time of the two-step aging treatment are determined as follows: the first step aging treatment is 1050-1120℃ / 4-6h, and the second step aging treatment is 850-870℃ / 16-20h.
[0056] The present invention is further described below by specific embodiments:
[0057] The following examples and comparative example 1 take ZGH451 alloy as an example to perform heat treatment on the additively manufactured nickel-based high-temperature alloy ZGH451. The chemical composition of the ZGH451 alloy is shown in Table 1.
[0058] Table 1 Chemical composition of ZGH451 alloy (wt%)
[0059] Alloying elements W Co Cr Mo Al Ti Ta C B Ni Content (wt) 8.0 8.0 8.0 2.0 4.1 1.2 5.5 0.01 0.015 margin
[0060] Example 1
[0061] This embodiment uses laser direct energy deposition process to prepare additively manufactured nickel-based high-temperature alloy ZGH451 specimens with high γ′ phase content; wherein the laser direct energy deposition process parameters are: power of 1700W, scanning speed of 1100mm / min, powder feeding speed of 10.5g / min, and laser diameter of 2mm. A rectangular column specimen with a length, width and height of 20mm×20mm×60mm is printed. Subsequently, the additively manufactured nickel-based high-temperature alloy ZGH451 specimen is heat treated and performance tested according to the following steps:
[0062] 1) Stress relief annealing: Heat the heat treatment furnace (box-type muffle furnace) to 870°C, place the additive manufacturing high-temperature alloy ZGH451 sample to be treated in the furnace for the first step of stress relief annealing, and keep the temperature for 2 hours; then heat the sample to 950°C with the furnace and then carry out the second step of stress relief annealing, and keep the temperature for 1 hour. Then take it out for air cooling and cool it to room temperature to obtain the additive manufacturing nickel-based high-temperature alloy sample after stress relief annealing.
[0063] 2) Solution treatment: The heat treatment furnace is heated to 1280°C, and then the additively manufactured nickel-based high-temperature alloy sample after stress relief annealing is placed in the furnace for solution treatment. The heat preservation time is 1 hour, and then it is taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy sample after solution treatment.
[0064] 3) Aging treatment: The heat treatment furnace is cooled to 1120°C, and then the additively manufactured nickel-based high-temperature alloy sample after the solution treatment is placed in the furnace for the first step of aging treatment. The insulation treatment time is 4 hours, and then it is taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy sample after the first step of aging treatment.
[0065] The heat treatment furnace was then cooled to 870°C, and the additively manufactured nickel-based high-temperature alloy sample after the first step of aging treatment was placed in the furnace for the second step of aging treatment. The insulation treatment time was 16 hours, and then the sample was taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy sample after heat treatment.
[0066] The additively manufactured nickel-based high-temperature alloy specimens after heat treatment were sliced and sent to a scanning electron microscope for observation. The microstructure achieved the expected effect and the heat treatment was completed.
[0067] The additively manufactured nickel-based high-temperature alloy specimens that have been fully heat-treated are processed into tensile and endurance specimens to complete mechanical properties testing.
[0068] Figure 1 Figure (a) shows the initial printed structure of the additively manufactured nickel-based high-temperature alloy ZGH451 sample (i.e., the deposited structure of the sample prepared by laser direct energy deposition process). In the deposited structure: the average grain size is 80-100μm, and there is dendrite segregation, where the primary dendrite spacing is 20-30μm.
[0069] Figure 2 1 is the alloy structure diagram of the additively manufactured nickel-based high-temperature alloy sample after heat treatment in Example 1.
[0070] contrast Figure 1 and Figure 2It can be seen that after the alloy is completely heat treated, the element segregation is significantly reduced, the dendrite / eutectic structure completely disappears, and the organization is crack-free and relatively uniform. In addition, a high content (volume fraction of 60%) and uniformly distributed cubic γ′ phase (γ′ phase has good cubicity and is obviously cubic) is precipitated in the heat-treated organization, with an average size of 0.45μm and an average grain size of 200μm. Therefore, good organization and precipitation phase characteristics are obtained through the heat treatment process of this embodiment.
[0071] The instantaneous tensile properties and endurance properties of the additively manufactured nickel-based high-temperature alloy in the deposited state and the heat-treated state of this embodiment are shown in Table 2.
[0072] Table 2
[0073]
[0074] It can be seen from Table 2 that from room temperature to 1000°C, the yield strength and tensile strength of the alloy after heat treatment in this embodiment are improved, and the plasticity is slightly reduced. Especially at a high temperature of 1000°C, the tensile strength of the alloy reaches 520MPa, which is significantly improved compared with the 460MPa in the deposited state, achieving further optimization of high temperature performance and exerting the potential excellent performance of the alloy. In addition, the endurance life of 760°C / 780MPa is also increased from 30h in the deposited state to 45h in the heat-treated state, with an increase of 50%. In summary, the heat treatment process of this embodiment achieves the optimization of alloy structure and performance, and achieves a significant performance breakthrough.
[0075] Example 2
[0076] This embodiment uses laser direct energy deposition process to prepare additively manufactured nickel-based high-temperature alloy ZGH451 specimens with high γ′ phase content; wherein the laser direct energy deposition process parameters are: power of 1700W, scanning speed of 1100mm / min, powder feeding speed of 10.5g / min, and laser diameter of 2mm. A rectangular column specimen with a length, width and height of 20mm×20mm×60mm is printed. Subsequently, the additively manufactured nickel-based high-temperature alloy ZGH451 specimen is heat treated and performance tested according to the following steps:
[0077] 1) Stress relief annealing: Heat the heat treatment furnace (box-type muffle furnace) to 890°C, put the additive manufacturing nickel-based superalloy ZGH451 sample to be treated into the furnace for the first step of stress relief annealing, and keep the temperature for 1 hour; then heat the sample to 950°C with the furnace and then carry out the second step of stress relief annealing, and keep the temperature for 1 hour. Then take it out for air cooling and cool it to room temperature to obtain the additive manufacturing nickel-based superalloy sample after stress relief annealing.
[0078] 2) Solution treatment: The heat treatment furnace is heated to 1270°C, and then the additively manufactured nickel-based high-temperature alloy sample after stress relief annealing is placed in the furnace for solution treatment. The insulation treatment time is 1 hour, and then it is taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy sample after solution treatment.
[0079] 3) Aging treatment: The heat treatment furnace is cooled to 1120°C, and then the additively manufactured nickel-based high-temperature alloy sample after the solution treatment is placed in the furnace for the first step of aging treatment. The insulation treatment time is 4 hours, and then it is taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy sample after the first step of aging treatment.
[0080] Subsequently, the heat treatment furnace was cooled to 850°C, and the additively manufactured nickel-based high-temperature alloy sample after the first step of aging treatment was placed in the furnace for the second step of aging treatment. The insulation treatment time was 20 hours, and then the sample was taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy after heat treatment.
[0081] The additively manufactured nickel-based high-temperature alloy specimens after heat treatment were sliced and sent to a scanning electron microscope for observation. The microstructure achieved the expected effect and the heat treatment was completed.
[0082] The additively manufactured nickel-based high-temperature alloy specimens that have been fully heat-treated are processed into tensile and endurance specimens to complete mechanical properties testing.
[0083] Figure 1 Figure (a) is the initial printed structure of the additively manufactured nickel-based high-temperature alloy ZGH451 sample (i.e., the deposited structure of the sample prepared by laser direct energy deposition process). Figure 3 This is the alloy structure diagram of the additively manufactured nickel-based high-temperature alloy sample after heat treatment in Example 2.
[0084] contrast Figure 1 and Figure 3 It can be seen that after the alloy is completely heat treated, the element segregation is significantly reduced, the dendrite / eutectic structure completely disappears, and the organization is crack-free and relatively uniform. In addition, a high content (volume fraction of 59%) and uniformly distributed cubic γ′ phase is precipitated in the heat-treated organization, with an average size of 0.40μm and an average grain size of 185μm. Good organization and precipitation phase characteristics are obtained through the heat treatment process of this embodiment.
[0085] The instantaneous tensile properties and endurance properties of the additively manufactured nickel-based high-temperature alloy prepared in this embodiment in the deposited state and the heat-treated state are shown in Table 3.
[0086] Table 3
[0087]
[0088] It can be seen from Table 3 that from room temperature to 1000°C, the yield strength and tensile strength of the alloy treated by the heat treatment process of this embodiment are improved, and the plasticity is slightly reduced, especially at a medium temperature of 760°C, the yield strength of the alloy reaches 894MPa, which is significantly improved compared with the 826MPa of the deposited state; at a high temperature of 1000°C, the tensile strength of the alloy reaches 507MPa, which is also significantly improved compared with the 460MPa of the deposited state, achieving further optimization of medium and high temperature performance and exerting the potential excellent performance of the alloy. In addition, the 760°C / 780MPa endurance life is also increased from 30h in the deposited state to 40h in the heat treated state, an increase of 33%. In summary, the heat treatment process of this embodiment achieves the optimization of alloy structure and performance, and has achieved a significant performance breakthrough.
[0089] Example 3
[0090] This embodiment uses laser direct energy deposition process to prepare additively manufactured nickel-based high-temperature alloy ZGH451 specimens with high γ′ phase content; wherein the laser direct energy deposition process parameters are: power of 1700W, scanning speed of 1100mm / min, powder feeding speed of 10.5g / min, and laser diameter of 2mm. A rectangular column specimen with a length, width and height of 20mm×20mm×60mm is printed. Subsequently, the additively manufactured nickel-based high-temperature alloy ZGH451 specimen is heat treated and performance tested according to the following steps:
[0091] 1) Stress relief treatment: The heat treatment furnace (box-type muffle furnace) is heated to 850°C, and the additive manufacturing nickel-based high-temperature alloy sample to be treated is placed in the furnace for stress relief annealing treatment, and the heat preservation time is 2 hours; then the sample is heated to 900°C with the furnace and then subjected to subsequent stress relief annealing treatment, and the heat preservation time is 2 hours. Then it is taken out for air cooling and cooled to room temperature to obtain the additive manufacturing nickel-based high-temperature alloy after stress relief annealing treatment.
[0092] 2) The heat treatment furnace is heated to 1280°C, and then the additively manufactured nickel-based high-temperature alloy sample after stress relief annealing is placed in the furnace for solution treatment. The heat preservation time is 1 hour, and then it is taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy after solution treatment.
[0093] 3) The heat treatment furnace is cooled to 1050°C, and then the additively manufactured nickel-based high-temperature alloy sample after the solid solution treatment is placed in the furnace for the first aging treatment. The heat preservation time is 6 hours, and then taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy after the first aging treatment.
[0094] The heat treatment furnace was then cooled to 870°C, and the additively manufactured high-temperature alloy sample after the first step of aging treatment was placed in the furnace for the second step of aging treatment. The insulation treatment time was 16 hours, and then the sample was taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy after heat treatment.
[0095] The additively manufactured nickel-based high-temperature alloy specimens after heat treatment were sliced and sent to a scanning electron microscope for observation. The microstructure achieved the expected effect and the heat treatment was completed.
[0096] The additively manufactured nickel-based high-temperature alloy specimens that have been fully heat-treated are processed into tensile and endurance specimens to complete mechanical properties testing.
[0097] Figure 1 Figure (a) is the initial printed structure of the additively manufactured nickel-based high-temperature alloy ZGH451 sample (i.e., the deposited structure of the sample prepared by laser direct energy deposition process). Figure 4 This is the alloy structure diagram of the additively manufactured nickel-based high-temperature alloy sample after heat treatment in Example 3.
[0098] contrast Figure 1 and Figure 4 It can be seen that after the alloy is completely heat treated, the element segregation is significantly reduced, the dendrite / eutectic structure completely disappears, and the organization is crack-free and relatively uniform. In addition, a high content (volume fraction of 61%) and uniformly distributed cubic γ′ phase is precipitated in the heat-treated organization, with an average size of 0.38μm and an average grain size of 190μm. Good organizational and precipitated phase characteristics are obtained through the heat treatment process of this embodiment.
[0099] The instantaneous tensile properties and endurance properties of the additively manufactured nickel-based high-temperature alloy prepared in this embodiment in the deposited state and the heat-treated state are shown in Table 4.
[0100] Table 4
[0101]
[0102] It can be seen from Table 4 that from room temperature to 1000°C, the yield strength and tensile strength of the alloy treated by the heat treatment process of this embodiment are improved, and the plasticity remains basically unchanged. At medium and high temperatures of 760°C and 1000°C, the yield and tensile strength of the alloy are slightly improved, and the alloy performance remains stable. In addition, the endurance life of 760°C / 780MPa is also increased from 30h in the deposited state to 35h in the heat-treated state. In summary, the heat treatment process of this embodiment achieves the optimization of alloy structure and performance.
[0103] Example 4
[0104] This embodiment uses a selective laser melting process to prepare an additively manufactured nickel-based high-temperature alloy ZGH451 sample with a high γ′ phase content; wherein the laser selective laser melting process parameters are: power 380W, scanning speed 800-1000mm / s, layer thickness 50μm, laser diameter 180μm, overlap rate 30%. Print out a rectangular column sample with a length, width and height of 20mm×20mm×60mm. Then, the additively manufactured nickel-based high-temperature alloy ZGH451 sample is heat treated and tested for performance according to the following steps:
[0105] 1) Stress relief annealing: Heat the heat treatment furnace (box-type muffle furnace) to 850°C, put the additive manufacturing high-temperature alloy ZGH451 sample to be treated into the furnace for the first step of stress relief annealing, and keep the temperature for 2 hours; then heat the sample to 900°C with the furnace and then carry out the second step of stress relief annealing, and keep the temperature for 1 hour. Then take it out for air cooling and cool it to room temperature to obtain the additive manufacturing nickel-based high-temperature alloy after stress relief annealing.
[0106] 2) Solution treatment: The heat treatment furnace is heated to 1250°C, and then the additively manufactured nickel-based high-temperature alloy sample after stress relief annealing is placed in the furnace for solution treatment. The heat preservation time is 2 hours, and then it is taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy after solution treatment.
[0107] 3) Aging treatment: The heat treatment furnace is cooled to 1050°C, and then the additively manufactured nickel-based high-temperature alloy sample after the solution treatment is placed in the furnace for the first aging treatment. The insulation treatment time is 6 hours, and then taken out for air cooling and cooled to room temperature to obtain the additively manufactured nickel-based high-temperature alloy after the first aging treatment.
[0108] The heat treatment furnace was then cooled to 870°C, and the additively manufactured nickel-based high-temperature alloy specimen after the first step of aging treatment was placed in the furnace for the second step of aging treatment. The insulation treatment time was 20 hours, and then the specimen was taken out for air cooling to room temperature.
[0109] The additively manufactured nickel-based high-temperature alloy specimens after heat treatment were sliced and sent to a scanning electron microscope for observation. The microstructure achieved the expected effect and the heat treatment was completed.
[0110] The additively manufactured nickel-based high-temperature alloy specimens that have been fully heat-treated are processed into tensile and endurance specimens to complete mechanical properties testing.
[0111] Figure 1 Figure (b) shows the initial printed structure of the additively manufactured nickel-based high-temperature alloy ZGH451 sample (i.e., the deposited structure of the sample prepared by the laser selective melting process). The average grain size is 20-50μm, and there are cellular structures and dendrites with a spacing of 5-10μm. Figure 5 This is the alloy structure diagram of the additively manufactured nickel-based high-temperature alloy sample after heat treatment in Example 4.
[0112] contrast Figure 1 Figure (b) and Figure 5 It can be seen that after the alloy is completely heat treated, the element segregation is significantly reduced, the dendrite / eutectic structure completely disappears, and the organization is crack-free and relatively uniform. In addition, a high content (volume fraction of 58%) and uniformly distributed cubic γ′ phase is precipitated in the heat-treated organization, with an average size of 0.35μm and an average grain size of 110μm. Good organizational and precipitated phase characteristics are obtained through the heat treatment process of this embodiment.
[0113] The instantaneous tensile properties and endurance properties of the additively manufactured nickel-based high-temperature alloy prepared in this embodiment in the deposited state and the heat-treated state are shown in Table 5.
[0114] Table 5
[0115]
[0116] It can be seen from Table 5 that from room temperature to 1000°C, the yield strength and tensile strength of the alloy treated by the heat treatment process of this embodiment are improved, and the plasticity is slightly reduced, especially at room temperature, the yield strength of the alloy is greatly improved, and at a high temperature of 1000°C, the yield and tensile strength of the alloy are slightly improved, achieving further optimization of the comprehensive performance. In addition, the 760°C / 780MPa endurance life is also increased from 20h in the deposited state to 25h in the heat-treated state, maintaining stable endurance performance. In summary, the heat treatment process of this embodiment achieves the optimization of alloy structure and performance.
[0117] Comparative Example 1
[0118] Comparative Example 1 provides the tensile properties of the ZGH451 alloy in the deposited state and in the heat-treated state using the traditional solid solution + homogenization + aging heat treatment process as shown in Table 6.
[0119] Table 6
[0120]
[0121] It can be seen that: since the ZGH451 alloy of comparative example 1 is subjected to traditional solid solution + homogenization + aging heat treatment, stress concentration is released, and a certain amount of cracks exist in the sample, which damages the alloy performance. Therefore, the room temperature, medium temperature, and high temperature tensile properties and plasticity of the additively manufactured nickel-based high-temperature alloys after heat treatment according to Examples 1-4 of the present invention are more significantly improved than the yield strength and tensile strength of comparative example 1, and the durability is more excellent, especially at 760°C and 1000°C in the medium and high temperature range, taking into account both strength and plasticity, the performance is greatly improved, which shows that the heat treatment process used in this embodiment can effectively achieve the regulation of good organization and excellent performance of additively manufactured nickel-based high-temperature alloys.
[0122] Comparative Example 2
[0123] Comparative Example 2 uses a laser direct energy deposition process to prepare an additively manufactured nickel-based high-temperature alloy ZGH451 sample with a high γ′ phase content. The main difference between Comparative Example 2 and Example 1 is that Comparative Example 2 adopts a one-step stress relief annealing treatment.
[0124] The instantaneous tensile properties and endurance properties of the additively manufactured nickel-based high-temperature alloy prepared in Comparative Example 2 in the deposited state and heat-treated state are shown in Table 7.
[0125] Table 7
[0126]
[0127] It can be seen that: after the ZGH451 alloy of comparative example 2 is subjected to one-step stress relief annealing + solution treatment + aging heat treatment, the stress release is still uneven due to the one-step stress relief annealing process with high temperature and drastic temperature changes, resulting in a small amount of cracks in the sample, which damages the alloy performance. However, the room temperature, medium temperature, and high temperature tensile properties and plasticity of the additively manufactured nickel-based high-temperature alloys after heat treatment according to Examples 1-4 of the present invention are more significantly improved than the yield strength and tensile strength of comparative example 2, especially at 760°C and 1000°C in the medium and high temperature range, taking into account both strength and plasticity, and the performance is greatly improved, which shows that the heat treatment process used in this embodiment can effectively achieve the regulation of good organization and excellent performance breakthrough of additively manufactured nickel-based high-temperature alloys.
[0128] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A heat treatment method for additively manufacturing a nickel-based high-temperature alloy, characterized in that: It includes the following steps: Stress relief annealing treatment: placing the additively manufactured nickel-based high-temperature alloy at a first temperature for a first step of stress relief annealing treatment; then heating it to a second temperature for a second step of stress relief annealing treatment, and after cooling, obtaining the additively manufactured nickel-based high-temperature alloy after the stress relief annealing treatment; wherein the first temperature is 850-890°C, and the second temperature is 900-950°C; Solution treatment: performing a solution treatment on the additively manufactured nickel-based high-temperature alloy after the stress relief annealing treatment to obtain the additively manufactured nickel-based high-temperature alloy after the solution treatment; Aging treatment: performing aging treatment on the additively manufactured nickel-based high-temperature alloy after the solid solution treatment to obtain the additively manufactured nickel-based high-temperature alloy after heat treatment.
2. The heat treatment method for additively manufactured nickel-based high-temperature alloy according to claim 1, characterized in that: In the step of stress relief annealing: The first step of stress relief annealing treatment takes 1-2 hours; and / or The second step of stress relief annealing treatment lasts for 1-2 hours; and / or The cooling method is air cooling, and the cooling is performed to room temperature.
3. The heat treatment method for additively manufactured nickel-based high-temperature alloy according to claim 1 or 2, characterized in that: In the step of stress relief annealing: The heat treatment furnace is heated to 850-890°C, and the additively manufactured nickel-based high-temperature alloy is placed in the heat treatment furnace for the first step of stress relief annealing treatment, and the insulation treatment time is 1-2 hours; then, the furnace is heated to 900-950°C and the second step of stress relief annealing treatment is carried out, and the insulation treatment time is 1-2 hours; finally, it is taken out for air cooling and cooled to room temperature.
4. The heat treatment method for additively manufacturing nickel-based high-temperature alloy according to any one of claims 1 to 3, characterized in that: In the step of solution treatment: The additively manufactured nickel-based high-temperature alloy after stress relief annealing is placed at a temperature of 1250-1280° C. for solution treatment, and then cooled to obtain the additively manufactured nickel-based high-temperature alloy after solution treatment; Preferably, the solution treatment time is 1-2h; Preferably, the cooling method is air cooling.
5. The heat treatment method for additively manufacturing nickel-based high-temperature alloy according to any one of claims 1 to 4, characterized in that: The aging treatment step includes: The first step of aging treatment: placing the additively manufactured nickel-based high-temperature alloy after the solid solution treatment at a temperature of 1050-1120° C. for the first step of aging treatment; after cooling, the additively manufactured nickel-based high-temperature alloy after the first step of aging treatment is obtained; The second step of aging treatment: placing the additively manufactured nickel-based high-temperature alloy after the first step of aging treatment at 850-870°C for the second step of aging treatment; after cooling, the additively manufactured high-temperature alloy after heat treatment is obtained; Preferably, the cooling method is air cooling; Preferably, cooling to room temperature.
6. The heat treatment method for additively manufactured nickel-based high-temperature alloy according to claim 5, characterized in that: In the aging treatment step: The temperature of the first step of aging treatment is 4-6h; and / or The temperature of the second step aging treatment is 16-20h.
7. The heat treatment method for additively manufacturing a nickel-based high-temperature alloy according to any one of claims 1 to 6, characterized in that: The additively manufactured nickel-based high-temperature alloy includes the following chemical components in terms of weight percentage: Cr 6.5-9.5wt%, Co 6.5-9.5wt%, W 6.5-9.5wt%, Mo1.0-2.5wt%, Al4.0-5.5wt%, Ti 0.5-1.5wt%, Ta 4.5-6.0wt%, C 0.01-0.1wt%, B 0.01-0.1wt%, and the balance is Ni.
8. The heat treatment method for additively manufacturing nickel-based high-temperature alloy according to any one of claims 1 to 7, characterized in that: The additively manufactured nickel-based high-temperature alloy is a deposited additively manufactured nickel-based high-temperature alloy; Preferably, the additively manufactured nickel-based high-temperature alloy is a deposited additively manufactured nickel-based high-temperature alloy prepared by laser direct energy deposition and selective laser melting; Preferably, if the additively manufactured nickel-based high-temperature alloy is a laser direct energy deposition alloy, then in the deposited structure: the average grain size is 80-100 μm, and there is dendrite segregation, wherein the primary dendrite spacing is 20-30 μm; Preferably, if the additively manufactured nickel-based high-temperature alloy is a selective laser melting deposited alloy, then in the deposited structure: the average grain size is 20-50 μm, and there is a cellular structure and dendrites with a spacing of 5-10 μm.
9. A nickel-based high-temperature alloy for additive manufacturing after heat treatment, characterized in that: The additively manufactured nickel-based high-temperature alloy after heat treatment is obtained by heat treating the additively manufactured nickel-based high-temperature alloy using the heat treatment method for additively manufactured nickel-based high-temperature alloy described in any one of claims 1 to 8.
10. The additively manufactured nickel-based high-temperature alloy after heat treatment according to claim 9, characterized in that: In the additively manufactured nickel-based high-temperature alloy after the heat treatment: the alloy structure is completely crack-free, the average size of the γ' phase is 0.3 μm-0.5 μm, the volume fraction is 55-65 vol%, and the average grain size is 100-200 μm; Preferably, the tensile properties of the additively manufactured nickel-based high-temperature alloy satisfy: at room temperature, σ b ≥1100MPa,σ 0.2 ≥900MPa, A≥10%; at 760℃±5℃, σ b ≥1050MPa,σ 0.2 ≥850MPa, A≥8%; at 1000℃±5℃, σ b ≥480MPa,σ 0.2 ≥290MPa, A≥8%.
Citation Information
Cited By
Method for inhibiting high-temperature brittle failure of laser additive manufacturing high-strength nickel-based alloy
CN120861841A
A method for inhibiting high-temperature brittle fracture of laser additive manufacturing high-strength nickel-based alloy
CN120861841B
Nickel-based high-temperature alloy block and continuous solution annealing method thereof
CN122466381A
A nickel-based superalloy block and a continuous solution annealing method thereof
CN122466381B